Influence of MSI and 18q LOH markers on capecitabine adjuvant monotherapy in colon cancer patients - Matevska Geshkovska, Nadica; Staninova Stojovska, Marija; Kapedanovska Nestorovska, Aleksandra; Petrushevska Angelovska, Natalija; Panovski, Milcho; Grozdanovska, Biljana; Mitreski, Nenad (Dove Press Ltd., 2018)
Purpose: The aim of this study was to evaluate whether pretreatment analysis of selected molecular markers can be used for the prediction of disease-free survival (DFS)/overall survival (OS) of capecitabine adjuvant monotherapy in colon cancer patients. Patients and methods: A total of 126 patients enrolled in a capecitabine Phase IV clinical trial were analyzed for microsatellite instability (MSI), 18q loss of heterozygosity (LOH), thymidylate synthase (TYMS) 5' variable number of tandem repeat (VNTR), and methylene tetrahydrofolate reductase (MTHFR) C677T variants. The significance in predicting 5-year DFS/OS was assessed by Kaplan-Meier and Cox regression analyses. Results: The MSI-high (MSI-H) genotype was significantly associated with DFS (HR 0.205, 95% CI 0.05-0.88, P=0.033) and OS (HR 0.208, 95% CI 0.05-0.89, P=0.035) compared to the microsatellite stable genotype. In models stratified according to clinicopathologic characteristics, the MSI-H genotype remained a positive predictive factor for DFS/OS only in patients with stage III (P=0.023) and patients with tumors localized proximally to the splenic flexure (P=0.004). Distal colon cancers with 18q LOH have a greater survival rate when treated with capecitabine than patients with stable tumors (81.3% vs 50.0%, HR for relapse 0.348, 95% CI 0.13-0.97, P=0.043). TYMS 5'VNTR and MTHFR C677T variants were not associated with DFS or OS. Conclusion: MSI and 18q LOH markers have the potential to be utilized in the selection of colon cancer patients eligible for capecitabine adjuvant monotherapy.
Keywords: 18q allelic imbalance; gastrointestinal cancer; microsatellite instability; prognostic marker